Law No. 174 of the Year 2023 On Granting Some Facilities to the Egyptians Residing Abroad = قانون رقم ١٧٤ لسنة ٢٠٢٣ بشأن تقرير بعض التيسيرات للمصريين المقيمين بالخارج - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic